STRATEGI PENGELOLAAN DANA KRABAT DALAM MENINGKATKAN PENDAPATAN PETANI (Studi Petani di Desa Pernek Kecamatan Moyo Hulu) - S Syafruddin; K Kurniawansyah; Ira Rianti (Pusat Riset dan Publikasi, 2021)
This study aims to know the strategy management of krabat funds in increasing farmers' income in Pernek Village, Moyo Hulu Sub-District. This study was qualitative. The methods used to collect data were through observations, interviews and documentation. The informants in this study were the Head Division of Economic Business Development and Inter-Village Cooperation of the Sumbawa District PMD office, Village Head of Pernek, the Manager of Village Owned Enterprise (BUMDES) of Pernek village, two customers whom received krabat fund. The type of data in this study was qualitative data, which was used as field data that seeks to see, to know and describe the reality. The results of study showed that the management of Krabat Fund of Sumbawa district in increasing farmers' income based on Regent Regulation No. 66 of 2019 and Standard Operational Procedures of Sahabat Fund Management had been done in Pernek Village but not yet maximized so that researchers formulated several new strategies that could be applied by Pernek BUMDes managers for sustainable management of Kerabat Fund namely: (a) building small banks at the village/district level (b) classifying non-performing loans (c) increasing cooperation with customers and the government (d) more detail in classifying communities into poor classification (f) increase the intensity of billing.